2005
DOI: 10.1007/s00595-004-2884-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Liver Function After Surgery for Budd-Chiari Syndrome

Abstract: Surgery during the early stage of BCS is important in improving postoperative liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…PH and liver function can be improved after early and effective treatment and long-term outcome of BCS is generally satisfied. [ 18 , 25 30 ] After interventional treatment for BCS, most of our patients have survived without notable symptoms of PH. Long-term survival of these patients is not clear because short follow-up duration, and it is also rarely reported elsewhere.…”
Section: Discussionmentioning
confidence: 97%
“…PH and liver function can be improved after early and effective treatment and long-term outcome of BCS is generally satisfied. [ 18 , 25 30 ] After interventional treatment for BCS, most of our patients have survived without notable symptoms of PH. Long-term survival of these patients is not clear because short follow-up duration, and it is also rarely reported elsewhere.…”
Section: Discussionmentioning
confidence: 97%
“…We previously described our corrective procedure for BCS that consists of reconstruction of the occluded IVC using autologous pericardium patch and reopening as many occluded hepatic veins as possible. [1][2][3] Malignant involvement of the IVC or superior vena cava (SVC) is sometimes surgically treated using autologous pericardium, which is considered good material for patch reconstruction after partial resection of the IVC or SVC. [4][5][6][7] We previously demonstrated that autologous pericardium is more effective than bovine or horse pericardium and expanded polytetrafluoroethylene (ePTFE) for reconstruction of the IVC in dogs.…”
mentioning
confidence: 99%